Comparative Pharmacokinetics, Bioequivalence and Safety Study of Two Recombinant Human Chorionic Gonadotropin Injections in Healthy Chinese Subjects - Wang J; Yang T; Mei H; Yu X; Peng H; Wang R; Cai Y (Drug Design, Development and Therapy, 2020)
Jin Wang,1,* Tianli Yang,1,* Hekun Mei,1 Xueming Yu,2 Hongmei Peng,3 Rui Wang,1 Yun Cai1 1Center of Medicine Clinical Research, Department of Pharmacy, PLA General Hospital, Beijing 100853, People’s Republic of China; 2Livzon MabPharm Inc, Zhuhai, Guangdong 519045, People’s Republic of China; 3Reproductive Medicine Center, Department of Obstetrics and Gynecology, PLA General Hospital, Beijing 100853, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun CaiCenter of Medicine Clinical Research, Department of Pharmacy, PLA General Hospital, 28 Fu Xing Road, Beijing 100853, People’s Republic of ChinaTel +86-10-6693-7166Email caicai_hh@126.comObjective: To evaluate the pharmacokinetics (PK), bioequivalence and safety profile of the recombinant human chorionic gonadotropin (r-hCG) injection formulation LZM003 (test drug) comparing with that of Ovidrel® (reference drug) in healthy Chinese subjects.Methods: This is a randomized, single-blind, single-dose, two-arm and two-period crossover Phase I study. Subjects were randomized evenly to a single dose of LZM003 or reference drug injected subcutaneously, with a 10-day or longer between-treatment washout period. PK parameters, anti-drug antibodies (ADAs), and adverse events (AEs) were assessed. The primary PK endpoints were area under the curve (AUC) of the concentration–time curve from zero to last quantifiable concentration (AUC0-t), AUC from zero to infinity (AUC0-∞), and peak concentration (Cmax). Bioequivalence was determined by assessing whether the 90% confidence intervals (CIs) for the geometric mean ratio (GMR) of LZM003 to reference drug fell within predefined margins of 80% − 125%.Results: Forty-eight subjects (24 males and 24 females) were enrolled and one subject withdrew for personal reasons. Mean values of primary PK parameters were similar (p > 0.05) between LZM003 and the reference drug. The 90% CIs for primary PK endpoints’ GMR of LZM003 to reference drug ranged between 0.9144 and 1.1845, which were within bioequivalence margins of 80− 125%. Incidence of AEs was similar (p > 0.05) between the two groups. Neither LZM003 nor reference drug produced anti-drug antibody (ADA) in healthy subjects.Conclusion: LZM003 and reference drug were bioequivalent. The PK and safety assessments were similar (p > 0.05) between the two formulations in healthy Chinese subjects.Trial Registration Number: ChiCTR-IIR-16010158 (http://www.chictr.org.cn).Trial Registration Date: December 15, 2016.Keywords: bioequivalence, human chorionic gonadotropin, Chinese subject, pharmacokinetics